Caracterización del uso y consumo del etiquetado nutricional tipo semaforización en la población ecuatoriana año 2019 - Armijos Benítez, Michelle Alejandra (2024)
In the Republic of Ecuador in 2013, the Sanitary Regulations for the Labeling of Processed Foods were implemented through the use of nutritional. The terminology HIGH in fat, sugar, and salt is shown in red, sugar and salt with the color red. The objective of the present investigation concerning. The aim of the present investigation for the red labeling of foods according to the nutritional traffic light in the Ecuadorian population in the year 2019 is to analyze the use, consumption, and correlation between the correlation between administrative levels of planning, sex, and ethnicity. For this purpose, a descriptive study was carried out, with a quantitative correlational methodological approach with a total sample of 43311 dwellings/households from the ENSANUT 2019 survey. This evidences that the use and consumption of these foods were higher in Zone 5 and 8 by 66.96%; according to sex, women with 33.50%; as for identification by ethnicity, mestizos are the group that most use red labeling when shopping, with 52.19%. The results of the correlation test (Pearson and Spearman) to evaluate the relationship between reduction and continued consumption of red-labeled foods by ethnicity show a negative correlation coefficient for both tests (-0.024 for Pearson and -0.026 for Spearman), with statistical significance (p < 0.0001). This suggests a slight negative correlation between reduced consumption and habitual consumption of red-labeled foods, indicating that while one part of the population is reducing its consumption, another continues to consume them